The Current Sentence in Surah Al-Imran: Ayat yang sedang dibacakan dalam Surah Al-Imran - Assist.Lect. Samer Rahim Fazea; Assist.Lect. Riyam Shalal Abbas (Academia Open, 2026)
General Background: Arabic grammar plays a fundamental role in interpreting Qur’anic texts and understanding their linguistic precision. Specific Background: The science of i‘rab provides detailed syntactic analysis that clarifies meaning and reveals the structural relationships between words in the Qur’an. Knowledge Gap: Despite the richness of classical grammatical sources, there remains a need for focused analytical studies that synthesize grammatical interpretations across authoritative works. Aims: This study aims to examine selected Qur’anic structures through grammatical analysis based on classical Arabic sources. Results: The findings show that variations in syntactic interpretation can lead to nuanced differences in meaning, supported by references to established grammatical authorities. Novelty: The study integrates multiple classical perspectives to provide a structured analysis of Qur’anic syntax. Implications: The results contribute to a deeper understanding of Qur’anic language and support further research in Arabic linguistics and textual interpretation. Keywords: Quranic Grammar, I'rab Analysis, Arabic Syntax, Classical Linguistics, Qur’anic Interpretation Key Findings Highlights Syntactic variation reflects multiple layers of meaning in scriptural language Classical grammatical sources provide complementary interpretive perspectives Structural analysis clarifies relationships between linguistic elements